Neural underpinnings of threat bias in relation to loss-of-control eating behaviors among adolescent girls with high weight - Byrne, Meghan E.; Tanofsky-Kraff, Marian; Liuzzi, Lucrezia; Holroyd, Tom; Parker, Megan N.; Bloomer, Bess F.; Nugent, Allison; Brady, Sheila M.; Yang, Shanna B.; Turner, Sara A.; Pine, Daniel S.; Yanovski, Jack A. (Frontiers in Psychiatry, 2023)
Loss-of-control (LOC) eating, a key feature of binge-eating disorder, may relate to attentional bias (AB) to highly salient interpersonal stimuli. The current pilot study used magnetoencephalography (MEG) to explore neural features of AB to socially threatening cues in adolescent girls with and without LOC-eating. Girls (12-17 years old) with overweight or obesity (BMI>85th%ile) completed an AB measure on an affective dot-probe AB task during MEG, and evoked neural responses to angry or happy (vs. neutral) face cues were captured. A laboratory test meal paradigm measured energy intake and macronutrient consumption patterns. Girls (N=34; Mage=15.5±1.5 years; BMI-z=1.7±0.4) showed a blunted evoked response to the presentation of angry compared to neutral face cues in the left dorsolateral prefrontal cortex, a neural region implicated in executive control and regulation processes, during attention deployment (p<.01). Compared to those without LOC-eating (N=21), girls with LOC-eating (N=13) demonstrated a stronger evoked response to angry faces in the visual cortex during attention deployment (p<.001). Visual and cognitive control ROIs had trends suggesting interaction with test meal intake patterns among girls with LOC-eating (ps=.01). These findings suggest that girls with overweight or obesity may fail to adaptively engage neural regions implicated in higher-order executive processes. This difficulty may relate to disinhibited eating patterns that could lead to excess weight gain.